(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2025)
Georgia has been a candidate country for EU membership since 2023, and the Association Agreement between Georgia and the European Union has been in force since 2016. Accordingly, Georgia is implementing reforms of the existing legislation and policies in the field of children’s rights, with the aim of implementing European and international standards. For this purpose, the Code of Rights of the Child was enacted in Georgia, which protects the right to life and health of the child and obliges the state to create guarantees for the protection of rights. Legislative reform involves harmonizing Georgian legislation with EU legislation, reflecting the requirements of various EU directives in Georgian legislation. One of such important areas is food safety and food product control, creating a healthy environment, which affects the realization of the right to life and health of the child. Despite the changes made to the legislation, non-compliance with regulations remains a problem. This paper analyzes Georgian legislation, European Union and international standards, and Georgian judicial practice regarding violations of the child’s right to life and health and presents specific recommendations for improving the protection of rights. Keywords: Child. European Union. Georgia, Healthcare. Food Safety.